Circumstances and Conditions in the Accreditation Process of University Degrees at the Albacete School of Industrial Engineering (Spain) - V. Miguel-Eguía; M. García-Teruel; J.A. Martínez-Martínez; F. García-Sevilla (Multidisciplinary Journal for Education, Social and Technological Sciences)
This work considers some of the main aspects involved during the period that elapsed between the validation of our degrees to the present time, which the School of Industrial Engineers of Albacete are currently under-going. One of the most disturbing factors has been teaching staff, who have been subjected to Spain’s economic circumstances. Other considerations, related to some difficulties of the re-accreditation process, have also been taken into account. Finally, we point out that although new learning methodologies were expected, the scope and the way Quality systems operate have arrived somewhat late.